Effects of countersunk hole geometry errors on the fatigue performance of CFRP bolted joints. (March 2022) - Qin, Xuda; Cao, Xingfeng; Li, Hao; Zhou, Meng; Ge, Ende; Li, Yonghang
Due to good aerodynamic performance and reliability, countersunk bolt joint is one of the most commonly used connection methods for carbon fiber reinforced polymer (CFRP) components in the aircraft. However, the countersunk hole machining process is inevitably accompanied by geometric errors, which will directly affect the mechanical properties of the joint structure. This paper presents a numerical and experimental investigation on the effect of countersunk hole geometry errors on the fatigue performance of CFRP bolted joints. FE model of CFRP countersunk bolted joints with designed geometry errors are established, and the rationality of the FE analysis was verified by fatigue life and failure forms. The CFRP bolted structure failure mechanism under fatigue load and influence of hole-making geometry error (including countersunk fillets radius, countersunk depth, and countersunk angle) on the fatigue life are investigated. Based on the relationship between fatigue life and the geometry error, the corresponding tolerances for CFRP bolt joint countersunk hole are determined as well. The research results can provide a reference for establishing reasonable geometric accuracy requirements for CFRP joint hole machining.